1) Разложим числитель и знаменатель дроби на множители
a² + 5a + 6 = a² + 2a + 3a + 6 = a(a+2) + 3(a+2) = (a+2)(a+3)
a² + 6a + 9 = (a+3)²
2) Снова же числитель и знаменатель дроби разложим на множители
5a² - 9a - 2 = 5a² - 10a + a - 2 = 5a(a-2) + a-2 = (a-2)(5a+1)
a² - 3a + 2 = a² - a - 2a + 2 = a(a-1) - 2(a-1) = (a-1)(a-2)
1) Разложим числитель и знаменатель дроби на множители
a² + 5a + 6 = a² + 2a + 3a + 6 = a(a+2) + 3(a+2) = (a+2)(a+3)
a² + 6a + 9 = (a+3)²
2) Снова же числитель и знаменатель дроби разложим на множители
5a² - 9a - 2 = 5a² - 10a + a - 2 = 5a(a-2) + a-2 = (a-2)(5a+1)
a² - 3a + 2 = a² - a - 2a + 2 = a(a-1) - 2(a-1) = (a-1)(a-2)